(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Science content and concepts concerning the nature of science (NOS) are two key aspects of scientific literacy, the promotion of which is the primary goal of general science education. However, the NOS, which acknowledges the human and societal aspects of science, is often neglected in favor of the content teachers are required to cover. The result is what Duschl (1990) calls “final-form” science, which presents science as a string of decontextualized facts and as settled knowledge. This common form of instruction leads students to develop misconceptions about NOS concepts by obscuring how scientific knowledge is developed by people. This essay argues that biographies of scientists, when carefully selected and implemented within the classroom, can be used to effectively teach both science content and NOS concepts, without requiring additional instruction time.